The Management of the City College of Calamba Towards the Attainment of the School’s Vision and Mission: A Basis for a Framework for Skills Enhancement Program - Montano, Mary Rose (Technium Social Sciences Journal, 2021)
The research was focused on the relationship of management functions of the administrators to the attainment of the school’s vision and mission because the researcher believed that it is possible for the College to accomplish and to attain the school’s vision and mission if only there will be direct participation, cooperation and coordination among administrators and staff. Specifically, it sought to find out the following: the effectiveness level of the said management functions of the school administrators and the different assessments on these matters by the two sets of respondents; the attainment level of the school’s vision and mission; the relationship, if there is any, between the two cited variables of the study; the frequency occurrence of the problems related to management functions; and the proposed framework for skills enhancement program. The respondents of the study were all 56 teaching staff and 17 non-teaching staff of the City College of Calamba. No sampling technique was used. Statistical treatments applied to the data of the study include the frequency and percent distributions in presenting the category of the respondents; the simple mean in determining the effectiveness level of the management practices, attainment level of the school’s vision and mission and the occurrence frequency of related problems; and the Goodman and Kruskal’s Gamma Correlation in establishing relationship between the two variables of the study. The research focused on three integrated elements comprised of the heart of every organization and its culture: its primary purpose; its desired future; and its core beliefs about itself and others. These serve as the “what to do and how to do” of every organization. Its achievement is the success and end-all, but this could only be attained if it is organized, operated and administered. According to the research result, the management functions of the CCC Administrators specifically, planning, organizing, leading and controlling were generally effective as assessed by the two sets of respondents. In the management functions of the School’s Administrators in relation to the attainment of CCC’s vision and mission the conducted correlation analysis generated a computed gamma coefficients of 0.577 and 0.729 which means that there are “high positive correlations” between the effectiveness of the management practices of the school administrators and the attainment both of the CCC’s vision and mission. Some related problems to the management functions of the school’s administrators were identified by both teaching and non-teaching staff such as: (1) poor learning environment – no air conditioning, insufficient space & lighting, and primitive toilet facilities (2) the work is not appropriately divided among faculty members and staff (3) they believe that the school administrators are the role policy maker in the school and (4) the teaching staff observe the existence of gap between the administrators and subordinates with a mean of 3.30 (sometimes), while the non-teaching staff was observed to withhold information (lie or tell half-truths) with a mean of 3.53 (sometimes). A proposed framework for skills enhancement program was formulated. It has the following: aspects of management for development, objective, activity, implementing strength, KRA indicator, performance indicator, budget and time. In the aspects of management for development, there are the four management practices – planning, organizing, leading and controlling. This was believed to be a great help for the administrators of City College of Calamba to improve the level of their effectiveness towards the attainment of the school’s vision and mission. Key words: public administration, management, effectiveness, efficiency, skills enhancement, development, descriptive method, city college